Enterprise system implementation and cash flow volatility - Liu, Alfred Z.; Pincus, Morton; Xu, Sean Xin (Contemporary Accounting Research, 2023)
Abstract This study investigates the financial and operational implications of enterprise systems (ESs) in corporate risk management. Using matched difference‐in‐differences analyses based on ES implementation events, we document a significant reduction in the volatility of operating cash flows following ES implementations. We further show that ES implementers have better post‐implementation operational efficiency than matched non‐ES firms and better manage sales, costs of sales, working capital, and operating expenses to reduce operating cash flow volatility. Consistent with the benefits of lower cash flow volatility documented in prior literature, we find ES implementers demonstrate higher investment efficiency, lower reliance on external financing, and higher debt capacity post‐ES‐implementation than the matched non‐ES firms. Our study sheds light on the economic benefits of utilizing ESs in corporate risk management and in so doing responds to the paucity of empirical research in this area.